Tsunami decision matrix for a strike-slip fault - The Gloria fault in the NE Atlantic - Guglielmin, Anna (Alma Mater Studiorum - Università di Bologna, 2023)
This thesis investigates the applicability of the Northeast Atlantic tsunami Decision Matrix to the unique characteristics of the Gloria Fault, a large strike-slip fault of the Azores-Gibraltar fracture zone that marks the western plate boundary between the Eurasian and Nubian plates. The objective of this research is to assess whether the existing decision matrix, designed for evaluating tsunami threat using basic earthquake parameters, can be effectively employed in the case of this specific fault. To achieve this, a comprehensive analysis is performed using a set of relevant earthquakes occurred in the 20th century along this fault or in its vicinities, namely the 25 November 1941 (Ms = 8.3), the 26th May 1975 earthquake (Ms = 7.9), the 1 January 1980 (Ms = 6.8). The only dip-slip event considered is the earthquake on February 28, 1969 (Ms = 7.9), that took place in the Horseshoe Abyssal Plain in the Gulf of Cadiz, while all the other events are strike-slip events. These seismic events, which had epicenters located in the North East Atlantic, along the Gloria Fault, will serve as key benchmarks for the Decision Matrix. The investigation encompasses several aspects, including the examination of historical tsunami data records, tsunami numerical simulations and applicability of Decision Matrix. Exhaustive examination of past tsunami occurrences provides valuable insights into the behavior and characteristics of tsunamis triggered by strike-slip faults. By studying the historical data, patterns and trends can be identified to enhance the decision matrix. The findings of this thesis contribute valuable insights to the field of tsunami real-time forecasting, offering a deeper understanding of the suitability and potential adaptations required for decision matrices when applied to strike-slip faults such as the Gloria Fault.